`f(x) = x^4 -4x^3 - 7x^2 + 28x`

`f(x) = x(x^3 -4x^2 - 7x +28)`

Break trinomial into groups: `(x^3-4x^2)` and `(-7x+28)`

` `Factor each: `x^2(x - 4)` and `-7(x - 4)`

Since both have factor of (x - 4) combine the 2 and the original x that was factored to get:

`f(x) = x (x - 4) (x^2-7)`

To find zeros of f(x), set the function equal to zero.

`x (x - 4) ( x^2 - 7) = 0`

Set each factor equal to zero and solve for x.

1) `x = 0`

2) `x - 4 = 0 rArr x = 4`

3) `x^2 - 7 = 0rArr x^2 = 7 rArr x =+-sqrt(7)` ` `

**The zeros to the function are: `0, 4,sqrt(7), -sqrt(7)` **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now